1992
DOI: 10.1136/oem.49.2.131
|View full text |Cite
|
Sign up to set email alerts
|

The possible haematological effects of glycol monomethyl ether in a frame factory.

Abstract: Haemopoietic effects of ethylene glycol monomethyl ether (EGME) are described in three young women employed in a frame factory where the substance was applied under apparently safe hygienic conditions. In a ventilated room they used a mixture of acetone (70%) and EGME (30%) to glue together cellulose acetate frame components. During a periodic medical examination their white blood cell count was found to be abnormally low, with a relative lymphocytosis, macrocytosis with red blood cells, and haemoglobin at bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 5 publications
3
20
0
3
Order By: Relevance
“…In the case of EGME, methoxy acetoaldehyde (MALD) and methoxy acetic acid (MAA) are formed, and are eliminated predominantly in the urine 2) . In hematopoiesis, there have been a limited number of case reports 3) showing mild macrocytic anemia and leukopenia, and laboratory animals exposed with these metabolites showed bone marrow hypocellularity resulting in pancytopenia 4) . However, the data on human bone marrow cells remain insufficient, and the mechanism of their toxicity has not been studied extensively 5) .…”
mentioning
confidence: 99%
“…In the case of EGME, methoxy acetoaldehyde (MALD) and methoxy acetic acid (MAA) are formed, and are eliminated predominantly in the urine 2) . In hematopoiesis, there have been a limited number of case reports 3) showing mild macrocytic anemia and leukopenia, and laboratory animals exposed with these metabolites showed bone marrow hypocellularity resulting in pancytopenia 4) . However, the data on human bone marrow cells remain insufficient, and the mechanism of their toxicity has not been studied extensively 5) .…”
mentioning
confidence: 99%
“…As far as we could determine, there are no reports on recovery from the hematological effects of 2-EE or 2-EEA in humans. Human case reports state that the hematological effect of 2-methoxy ethanol (2-ME), a structurally similar ethylene glycol ether to 2-EEA, quickly dissipates to normal, within 4 wk to 3 months after cessation of exposure [29][30][31][32][33][34] . Our recent paper also showed that subjects recovered very quickly from the 2-ME-induced hematological effects as the airborne concentrations of 2-ME and its major toxic metabolite, MAA (2-methoxy acetic acid), were reduced 35,36) .…”
Section: Discussionmentioning
confidence: 99%
“…In this disorder, severe cases of bone marrow disorders presenting as severe pancytopenia are very rare. However, mild cases of bone marrow disorders are hard to be detected because peripheral blood findings are not helpful in predicting the bone marrow damage in these cases 6,11) . Examination of the peripheral blood is a routine method for the screening of hematologic disorders, but it does not reflect the cellularity of the bone marrow directly.…”
Section: Industrial Health 2004 42 179-188mentioning
confidence: 99%